(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
Checco Zalone is one of the most important phenomena of Italian Cinema of the last decades. One of the constants of his cinema is the presence of the song-form, in particular of original songs (original soundtrack), used as a mean to transit from the theatre, radio and TV to the cinema: this paper constitutes a sociosemiotic, interdisciplinary and culturalist analysis of the different expressive modalities with which Zalone makes use of his songs, that become a configuration element of his own style, representing a specific cinematographic way and strengthening Zalone’s authorial role in his cinema in a complex and considerable way.